An Empirical Investigation Between Money Supply, Inflation, Capital Expenditure and Economic Growth in Nepal (Quest Journal of Management and Social Sciences, 2021)
Background: Money supply, inflation, and capital expenditure along with others are major issues of consideration for policymakers in developing countries given the need to spark internal demand and to encounter the government’s massive fiscal obligations to alleviate poverty and achieve sustainable economic growth. Like other economies, the economic performance of Nepal is also based on these macroeconomic variables. Objective: The principal objective of the study is to explore the association between money supply, inflation, capital expenditure, and economic growth in Nepal.Method: The study applies the ARDL approach to co-integration to check the relationship between selected variables. The bound test is carried out to see the relationship between variables.Result: The empirical findings of the study show that there is a significant long-run positive relationship between money supply, capital expenditure, and growth. There is a unidirectional causation from money supply and capital expenditure to real economic growth in Nepal.Conclusion: The study concludes that an increase in money supply, capital expenditure, and controlling inflation help to increase the long-run real economic growth of Nepal. Nepal Rastra Bank has to emphasize monetary policy instruments that help to increase the money supply in the long run and the Ministry of Finance (MoF) should be encouraged to increase spending on capital overheads to broaden and enhance the growth of the economy.